Total volvulus of the small intestine in a patient with a previous right hemicolectomy: (Mass resection with survival) - Rossi, Juan J. (Cirugía del Uruguay, 1986)
This communication refers to a previously hemicolectomized patient, who underwent massive resection of the small intestine. The clinical condition was that of a mechanic intestinal occlusion with persistent shock. Surgical exploration revealed total volvulus of small intestine that resulted in total infarction of same. Surgical treatment consisted in almos! total resection of the jejunal ileum. Seven years alter operation, the palient discharges her intestine two or three times a day, defecating soft matter and her activities are practically normal.